Audio power amplifier design handbook - Self, Douglas (Oxford ; Boston : Newnes, 2002)
Douglas Self has called upon his years of experience at the cutting edge of audio design to compile this handbook for professionals and students. The book provides a clear and practical guide to the state of the art, and includes detailed design and construction information. This new edition is more comprehensive than ever, with a new chapter on Class G amplifiers and further new material on output coils, thermal distortion, relay distortion, ground loops, triple EF output stages and convection cooling. Douglas Self has dedicated himself to demystifying amplifier design and establishing empirical design techniques based on electronic design principles and experimental data. His rigorous and thoroughly practical approach has established him as a leading authority on amplifier design, especially through the pages of Electronics World where he is a regular contributor. * Discover the secrets of cutting-edge audio design * The definitive professional handbook for amplifier designers * Includes a new chapter on Class G amplifiers.
Preface; Introduction and general survey; History, architecture and negative feedback; The general principles of power amplifiers; The small signal stages; The output stage I; The output stage II; Compensation, slew-rate, and stability; Power supplies and PSRR; Class-A power amplifiers; Class-G power amplifiers; FET output stages; Thermal compensation and thermal dynamics; Amplifier and loudspeaker protection; Grounding and practical matters; Testing and safety; Index.
Includes bibliographical references and index.
Keywords: Audio amplifiers -- Design and construction; Power amplifiers -- Design and construction; Audio amplifiers -- Design; Power amplifiers -- Design; Electronic books